Pengaruh Kebutuhan Sosial dan Budaya Kerja Terhadap Kepuasan Kerja - Isra, Muh; Herniah, Herniah; Normiyati, Normiyati (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2025)
This research is a quantitative descriptive study that aims to analyze the effect of social needs, work culture on job satisfaction at PT Aneka Jasa Sorowako in Makassar. This study uses primary data obtained by distributing questionnaires to 36 respondents. To analyze the data, the authors used multiple linear regression analysis tools. Based on the results of calculations using the SPSS program, it was found that the t value was 4.281 for the social needs variable. Meanwhile, the work culture variable found a t value of 5.545 with a significance value of 0.001 for each variable. This shows that social needs and work culture have a positive and significant effect on employee job satisfaction.